Voting and the Scottish referendum: perspectives of people with intellectual disabilities and their family and paid carers. Issue 7 (8th August 2016) - Willis, Diane S.; McGlade, Isla; Gallagher, Mark; Menabney, Colin
Abstract: Voting is a human right for every citizen yet many people with intellectual disabilities do not vote or have little support to exercise their right to vote. This article explores views on the wider aspects of voting against the backdrop of the Scottish referendum using focus groups involving people with intellectual disabilities ( n = 12), family carers ( n = 7) and paid carers ( n = 5). Findings revealed that people with intellectual disabilities had similar concerns to the general population about the referendum. Regarding voting, all groups identified the need to discuss issues and for practical support and accessible information to ensure informed choices were made when voting.